IN VITRO STUDY OF ANTITRYPANOSOMAL ACTIVITY OF ETHANOLIC LEAF EXTRACT OF GARCINIA KOLA AGAINST TRYPANOSOMA BRUCEI BRUCEI - Sani, Ali; Zakariyya, Umar Abdullahi; Mahe, Asmau; Singh, Deepa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was aimed at evaluating in vitro antitrypanosomal activity of Garcinia kola against Trypanosoma brucei brucei. Methods: The plant materials were extracted and screened for phytochemicals. The antitrypanosomal activity of 70% and 100% G. kola extracts against the parasite was determined in vitro. Results: Both extracts contained saponins, tannins, carbohydrates, cardiac glycosides, and flavonoids. However, anthraquinones and alkaloids were undetected. The parasites were seen to be actively motile within the first 30 min post-incubation period in 70% hydroethanolic G. kola extract and were found dead at 40–60 min in a higher concentration of extract. After 10 min post-incubation of the parasites in 100% ethanolic extract of G. kola, the parasites were observed to be active at lower concentration but at higher concentrations of the extracts, no trypanosomes were seen. Conclusion: 100% extract induces ceasing of motility at the lesser time compared to 70% ethanolic extract. Similarly, the effect increases with increase in extract concentration. Further research should be carried out to elucidate the bioactive compounds present to have a broad knowledge on the mode of action of the compounds.